PENERAPAN PEMBELAJARAN KLINIK MELALUI MODEL MOVING CLASS TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - SOLCHAN GHOZALI (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2019)
Your successtowards quality education, one of the assessments can be seen from the success in the learning process. Learning success can be seen from student motivation and learning outcomes. Most students feel saturated when in the middle of the learning process which results in a decrease in learning motivation. In order not to be boring, teachers should need to provide clinical learning activities using the moving class model so that students can be motivated in learning. The purpose of this study is to determine the influence of the application of clinical learning through the moving class model on the motivation and learning outcomes of grade IV MINU Waru 1 Sidoarjo students. The method in this study is a quantitative method. The data collection techniques used are sngket (questionnaire) and documentation. Based on the results of the study proved that: There is no influence of the application of clinical learning through the moving class model on learning outcomes. The interpretation results have no correlation and there is no influence between clinical learning through the moving class model on learning outcomes.  this is in accordance with the results of the analysis using pearson correlation analysis, namely- 0.009 which means that there is no correlation between the application of clinical learning through the moving class (X) model to learning outcomes (Y2). Then the interpretation results are at an average below 0.00 which means that it shows no correlation